Extensive functional evaluation of exon 20 insertion mutations of EGFR. (February 2021) - Hirose, Takeshi; Ikegami, Masachika; Endo, Makoto; Matsumoto, Yoshihiro; Nakashima, Yasuharu; Mano, Hiroyuki; Kohsaka, Shinji
Highlights: The transforming potential and drug sensitivities of 21 EGFR exon 20 insertions were evaluated. EGFR exon 20 insertions were shown to have different degrees of sensitivity to EGFR tyrosine kinase inhibitors. Some exon 20 insertions showed higher sensitivity to osimertinib, poziotinib and mobocertinib than gefitinib and afatinib. Abstract: Objectives: Exon 20 insertion mutations of epidermal growth factor receptor (EGFR) have been identified as oncogenic mutations in general; however, the functional relevance of each remains largely uninvestigated. Herein, we comprehensively assessed the functional significance of insertion mutations of EGFR exon 20. Materials and methods: The transforming potential and drug sensitivities of 25 EGFR recurrent mutants, including twenty-one exon 20 insertions, were evaluated using the mixed-all-nominated-in-one method. Results: The sensitivity of EGFR exon 20 insertions to EGFR tyrosine kinase inhibitors (TKIs) was generally lower than that of the L858R mutation or exon 19 deletions. The results were also confirmed through an in vivo drug test. All of the exon 20 insertions were resistant to gefitinib and afatinib, whereas several mutants were sensitive to osimertinib. EGFR exon 20 insertions exhibited relatively good responses to poziotinib and mobocertinib. Conclusions: EGFR exon 20 insertions were shown to have different degrees of sensitivity to EGFR TKIs. This extensive assessment of EGFR exon 20 insertions may provide a fundamental database for aiding in a customized mode of therapy for cancers having insertional mutations within exon 20 of EGFR, although the clinical impact of preclinical data should be validated by clinical evidence in the future.